2018
DOI: 10.1172/jci99507
|View full text |Cite
|
Sign up to set email alerts
|

CaMK4 compromises podocyte function in autoimmune and nonautoimmune kidney disease

Abstract: Podocyte malfunction occurs in autoimmune and nonautoimmune kidney disease. Calcium signaling is essential for podocyte injury, but the role of Ca2+/calmodulin-dependent kinase (CaMK) signaling in podocytes has not been fully explored. We report that podocytes from patients with lupus nephritis and focal segmental glomerulosclerosis and lupus-prone and lipopolysaccharide- or adriamycin-treated mice display increased expression of CaMK IV (CaMK4), but not CaMK2. Mechanistically, CaMK4 modulated podocyte motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 40 publications
5
63
0
Order By: Relevance
“…PLGA NPs encapsulating tolerogenic peptides or peptides and rapamycin that targeted APCs prevented or reversed disease in animal models of autoimmune diabetes and multiple sclerosis through TGFβ‐dependent induction of Treg cells . Moreover, NP‐mediated delivery of the immunosuppressive drug Ca 2+ /calmodulin‐dependent protein kinase IV inhibitor ameliorated murine SLE .…”
Section: Discussionmentioning
confidence: 99%
“…PLGA NPs encapsulating tolerogenic peptides or peptides and rapamycin that targeted APCs prevented or reversed disease in animal models of autoimmune diabetes and multiple sclerosis through TGFβ‐dependent induction of Treg cells . Moreover, NP‐mediated delivery of the immunosuppressive drug Ca 2+ /calmodulin‐dependent protein kinase IV inhibitor ameliorated murine SLE .…”
Section: Discussionmentioning
confidence: 99%
“…Calcium/calmodulin-dependent protein kinase IV (CaMK4) is a multifunctional serine/threonine kinase that regulates the expression of several genes (12)(13)(14). Previously, we have shown that CaMK4 is increased in the nuclei of T cells from patients with SLE (15) and is necessary for Th17 differentiation (13).…”
Section: Introductionmentioning
confidence: 99%
“…Neither their study nor our previous study observed labeled LPS binding or accumulation in the distal tubules during endotoxemia. 3 LPS in the glomeruli diminished the glomerular filtration barrier 22 and may affect the fluid filtration rate. However, the reduction in the tubular flow rate in the proximal tubules occurred immediately after LPS exposure (<2 hours) while the GFR was still preserved, 3 and urine volume was almost normalized in proximal tubular TLR4-KO mice.…”
Section: Discussionmentioning
confidence: 95%